‘Coming out’ across cultures: examining the experiences of Ecuadorian and Spanish LGB employees - Corlett, S.; Di Marco, D.; Arenas, A. (Current Psychology, 2021)
Lesbian, gay and bisexual (LGB) employees use the invisible character of their sexual identity to adopt strategies that reveal or hide their sexual orientation at work. Previous research has focused on environmental and individual factors that play a role in the disclosure process of LGB employees, yet cultural factors that may also impact this process have remained practically ignored in the literature. In this study we analyze the disclosure process of 15 Spanish and 15 Ecuadorian LGB individuals through in-depth semi-structured interviews. The results suggest that some cultural elements in each country, such as religion and gender role norms, make the experiences of the participants dissimilar. The consequences of adopting different disclosure strategies have been found for both the individual (e.g., relationship with colleagues, well-being) and organizations (e.g., performance). This study highlights the need for research to find effective measures to include LGB people in organizations and encourages researchers to adopt a cultural approach when studying the process of disclosure at work.